Somatic mosaicism in adult‐onset TNF receptor‐associated periodic syndrome (TRAPS) - Apostolos Kontzias; Samaneh K. Zarabi; Cassandra Calabrese; Yan Wang; LuAnn Judis; QingPing Yao; Yu‐Wei Cheng (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Somatic mosaicism is to date an uncommon finding in genetic autoinflammatory syndromes such as Cryopyrin‐associated periodic syndrome, Blau syndrome, and TNF receptor‐associated periodic syndrome (TRAPS). However, somatic mosaicism may be particularly important in adult‐onset or atypical phenotypes of these conditions. Herein, we report a unique adult‐onset TRAPS patient presenting with intermittent daily fever for 3 weeks, rash, peritonitis, and lymphadenopathy, who was found with hematopoietic mosaicism involving different white blood cell populations. Methods Patient's lymphocyte genomic DNA was initially analyzed by periodic fever seven‐gene next‐generation sequencing panel. Genomic DNAs extracted from patient's hair roots, buccal swab, and subpopulations of white blood cells were subsequently examined on the identified TNFRSF1A variant using Sanger sequencing. Results A de novo mosaic missense variant, c.265 T>C(p.Phe89Leu), in the TNFRSF1A gene was found in the patient's buccal swab, B cells, neutrophils, and NK cells but not detected in monocytes, T cells, and hair roots. Conclusion These data provide additional information about somatic mosaicism in autoinflammatory conditions and provide new insights regarding cellular players that are indispensable for the phenotypic expression of TRAPS.